The Effect of Weevil Elaeidobius kamerunicus population (Coleoptera: Curculionidae) In Female Flowers of Palm Oil (Elaeis guineensis Jacq) towards Fruit Set Formation - RAMADHAN (NIM : 11413050), GILANG
The E. kamerunicus weevil (Coleoptera: Curculionidae) is one of the most effective pollinators to pollinate the palm oil flower. These insects have been proven to increase the productivity of oil palm. A research has been conducted to investigate the effect of E. kamerunicus population who visited the female flower on an 8-year-old palm oil plant in PTPN VIII, Sukabumi. Observations were conducted on 30-32 bunches of female flowers in 8 plots (1 plot = Ã‚Â± 0.2 Ha). Male and female flower ratios were calculated directly in the entire areas. The weevil population visiting the female flower was conducted between 07.00 am to 16.00 pm by direct count on female flowers of palm oil tree by using hand counter. The percentage of fruit sets formed was calculated 6 months after the observation of weevil population. The results indicated that the amount of female flowers were more than the male flowers. E. kamerunicus began to visit the female flowers in the morning, reaching the peak between 11:45 to 12:45 then decreased after 16.00. The average of E. kamerunicus population which visited the highest female flower occurred between 12:00 to 12:15, with the amount of 84.5 individuals/ flower. The average percentage of fruit set formed was amounted to 73.64%, the number was positively correlated (r = 0.37). From the results of the research, it may be concluded that the visit of weevil E. kamerunicus has an effect towards the increase of oil palm fruit set.